Leukocytes Enhance Inflammatory and Catabolic Degenerative Changes in the Intervertebral Disc After Endplate Fracture In Vitro Without Infiltrating the Disc. Issue 23 (December 2015) - Dudli, Stefan; Boffa, Davide B.; Ferguson, Stephen J.; Haschtmann, Daniel
Abstract : Study Design: An established rabbit intervertebral disc (IVD)/endplate explant fracture model was extended with physiologic post-traumatic dynamic loading (PTDL) and coculturing of peripheral blood mononuclear cells (PBMCs). Objective: The aim of this study was to quantify the effects of PTDL and of cocultured PBMCs on post-traumatic disc degeneration (DD) and to determine whether PTDL facilitates homing of PBMC to fractured IVD/endplates. Summary of Background Data: DD is associated with endplate fracture. In vivo studies suggest a key role of immune cells in the pathogenesis of DD. However, the complexity of in vivo systems impedes the investigation of single factors governing the pathogenesis. Methods: Seventy-two IVD/endplate specimens were divided into 4 groups. In group A, endplate fractures were induced with a high-velocity axial load and exposed to PTDL in coculture with PBMCs for 14 days. Group A was compared with 3 control groups, with single-factor removal, in order to assess the relative contribution of PTDL (group B), PBMCs (group C), and endplate fracture (group D) to the biological response of the IVD. Disc gene transcription and serum nitric oxide (NO) serum concentration were measured to investigate differences in anabolism, catabolism, and inflammatory response between the groups. Changes in matrix composition and disc structure were assessed histologically. Results: PBMCs did not home to fractured IVDs, with or without PTDL. Group A compared with group D showed an enhanced transcription of anabolic, catabolic, and pro-inflammatory genes during the entire experiment, and an increased NO concentration for the first 3 days. Changes typical for DD were also found in histological sections. Group A compared with group C showed significant increases in catabolic and pro-inflammatory gene transcription after at least 7 days. No differences were found between groups A and B. Conclusion: Trauma induces degenerative changes; PTDL neither aggravates nor ameliorates this response. Although PBMCs do not infiltrate the disc, they aggravate the degenerative changes. Level of Evidence: N/A Abstract : Supplemental Digital Content is available in the text